2000
DOI: 10.1038/sj.bjp.0703249
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3‐receptor antagonists inhibit gastroprotection by (R)‐α‐methylhistamine in the rat

Abstract: (R)‐α‐methylhistamine, a selective agonist of histamine H3 receptors, is capable of protecting the gastric mucosa against differently acting damaging agents. The objective of the present study was to determine whether H3 receptors mediate its protective action in the rat. Gastric mucosal lesions were induced intragastrically (i.g.) by 0.6 N HCl, 1 ml rat−1. (R)‐α‐methylhistamine, 100 mg kg−1 i.g., substantially reduced the severity of macroscopically and histologically assessed damage caused by concentrated ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
2
9
1
Order By: Relevance
“…In particular, the involvement of H 3 Rs was ruled out based on the ineffectiveness of the H 3 R antagonist clobenpropit. As opposed to the study by Konturek et al [30] , our data clearly suggest that histamine released by ghrelin activates H 3 Rs to afford protective effects, in accordance with literature data [31][32][33][34] . The reason for this discrepancy may possibly be attributed to the use of clobenpropit; indeed, it has recently been demonstrated that this compound, originally described as a potent and highly selective H 3 R antagonist [35] , also displays affinity for the newly discovered H 4 R, behaving as a partial agonist in functional assays [36] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, the involvement of H 3 Rs was ruled out based on the ineffectiveness of the H 3 R antagonist clobenpropit. As opposed to the study by Konturek et al [30] , our data clearly suggest that histamine released by ghrelin activates H 3 Rs to afford protective effects, in accordance with literature data [31][32][33][34] . The reason for this discrepancy may possibly be attributed to the use of clobenpropit; indeed, it has recently been demonstrated that this compound, originally described as a potent and highly selective H 3 R antagonist [35] , also displays affinity for the newly discovered H 4 R, behaving as a partial agonist in functional assays [36] .…”
Section: Discussionsupporting
confidence: 63%
“…The involvement of histamine in the acid secretory and protective effects of ghrelin is a matter of debate: an increase in histidine decarboxylase expression in the rat gastric mucosa after peripheral administration of ghrelin was not unanimously detected [16,27,30] ; moreover, the study by Konturek et al [30] ruled out a role for histamine H 3 receptors (H 3 Rs) in the action of ghrelin, as the H 3 R antagonist clobenpropit did not modify ghrelin-induced gastroprotection. This was rather unexpected since previously published data have clearly shown that the histamine H 3 R subtype is predominantly involved in gastric mucosal protection [31][32][33][34] . The use of clobenpropit is questionable since this compound, originally described as a highly selective H 3 R antagonist [35] , displays affinity for histamine H 4 receptors (H 4 Rs) [36] ; as this last receptor has been recently involved in ulcerogenesis [37] , further studies employing more selective H 3 R ligands are required in order to identify the histamine receptor subtype involved in the gastric effects of ghrelin.…”
mentioning
confidence: 69%
“…We previously showed that the selective agonist of histamine H 3 receptors, (R)‐α‐methylhistamine ((R)α‐MeHA) (Arrang et al ., 1987), protects the gastric mucosa against acute damage from differently acting noxious agents in the rat (Morini et al ., 1995; 1997b). Its protective effect is reversed by the highly selective H 3 receptor antagonists clobenpropit and ciproxifan (Ligneau et al ., 1998; Morini et al ., 2000). Ethanol‐induced total damage was not reduced by the S isomer of α‐methylhistamine ((S)α‐MeHA (Morini et al ., 1999), as expected on the basis of the high degree of stereoselectivity of H 3 receptors (Arrang et al ., 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of central H 3 receptors also induced gastroprotective effect [133]. The role of H 3 receptors in gastric mucosal integrity was confirmed by the findings that antagonists of H 3 receptor aggravated the HCl-induced mucosal lesions [134].…”
Section: Histamine Receptorsmentioning
confidence: 88%
“…(R) alpha-methyl histamine -selective agonist of H 3 receptor -given orally induced mucosal protection against absolute ethanol, HCl, aspirin and stress [132,133]. The protective effect was antagonized by the H 3 receptor selective antagonists ciproxifan and clobenpropit [134]. The gastroprotective effect is likely to be due to increased mucus production via nitric oxide dependent pathway.…”
Section: Histamine Receptorsmentioning
confidence: 98%